(untitled) - Maimon, Elaine P. (New York, 2012)
This hardcover version of the comprehensive McGraw-Hill Handbook includes foldouts on documentation/sourcing, and new sections including "Start Smart" to help students know where to begin and how to navigate the writing situation for all their common assignments. The Maimon handbooks support student and instructor success by consistently presenting and using the writing situation as a framework for beginning, analyzing and navigating any type of writing. Start Smart offers an easy, step-by-step process map to navigate three common types of writing assignments. Other new features support critical thinking and deeper understandings of common assignments. Its digital program addresses critical instructor and administrator needs – with adaptive diagnostic tools, individualized learning plans, peer review, and outcomes based assessment. Connect Composition will also fully integrate into the Blackboard CMS for single sign on and autosync for all assignment and grade book utilities.
Keywords: English language,Tiếng Anh; Rhetoric,Tu từ học